Transfer of 3D Scanning Technologies Into the Field of Criminal Proceedings - Blahuta, R.I.; Blikhar, V.S.; Dufenіuk, O.M. (Наука та інновації, 2020)
Introduction. Everyday, hundreds ideas of innovative technologies are developed, and thousands innovative
products and services are implemented. The practice of criminal proceedings does not stand aside these processes.
In recent years, foreign specialists have been increasingly focusing on 3D scanning technologies and the potential
of their use in investigations.
Problem Statement. The problem of 3D technologies in the criminalistic practice has not been sufficiently
developed in Ukrainian science, and the idea of using 3D technologies for fixing evidence, as well as tracing the
evidence and corpus delicti is only at the initial stage of development. In the future, focus on active implementation
of 3D scanning technologies in forensic activities is expected to increase.
Purpose. On the basis of generalization of international experience, a systematic review of the advantages of
using 3D scanning technologies in criminal proceedings has been carried out, and the prospects for the transfer of
these innovations to the criminalistic practice in Ukraine have been outlined.
Materials and Methods. Comparative analysis, formal and logical methods.
Results. The use of 3D scanning technologies is a unique way of fixing the information about a criminal offense,
which provides access to the virtual image of the crime scene for all participants of the criminal process. An
investigator, a prosecutor, a judge, and a juror can visualize the crime scene using 3D model. The advantages of
this process are universality, portability, agility, ease of use, efficiency, safety, multi-functionality, and cost effectiveness.
Conclusions. The world practice of police services has proved the expediency of using laser scanning while
investigating criminal offenses. Ukraine is also expected to make a progress in the technological support of
police and expert services, insofar as effective counteraction to modern crimes without innovations is an impossible
mission. Вступ. Щодня розробляються сотні ідей інноваційних технологій, впроваджуються тисячі інноваційних продуктів та
послуг. Не залишалася осторонь цих процесів і сфера кримінального провадження. Останнім часом іноземні фахівці
дедалі більше увагу приділяють технології 3D-сканування та потенційним можливостям її використання у ході розслідування.
Проблематика. Тема 3D-технологій у криміналістичній діяльності в українській науці розроблена недостатньо, а
ідея використання 3D-технологій для фіксації доказової інформації, дослідження слідів та речових доказів перебуває
тільки на початковій стадії розробки. В майбутньому зацікавленість до активного впровадження технологій 3D-сканування у криміналістичну діяльність буде тільки зростати. Мета. Системний огляд переваг застосування технологій 3D-сканування у кримінальному провадженні на підставі узагальнення міжнародного досвіду, а також окреслення перспективи впровадження зазначених інновацій
в Україні. Матеріали та методи. Компаративний аналіз, формально-логічні методи.
Результати. Застосування технологій 3D-сканування — це унікальний спосіб фіксації інформації про кримінальне
правопорушення, що забезпечує доступ до віртуального зображення місця події усім учасникам кримінального процесу. Слідчий, прокурор, слідчий суддя, суддя, присяжний можуть, переглядаючи 3D-модель унаочнити місце події.
При цьому основними перевагами застосування такого підходу обробки інформації є: універсальність, портативність,
швидкість, легкість у використанні, оперативність, безпечність, поліфункціональність та економічність.
Висновки. Світова практика роботи поліцейських служб доводить доцільність застосування лазерного сканування під час розслідування кримінальних правопорушень. В Україні також слід очікувати прорив у технологічному
розвитку криміналістичного забезпечення діяльності поліції та експертних служб.